LEAF CHARACTERISTICS OF BETELVINE (PIPER BETLE L.) AS INFLUENCED BY CLIMATE - H. MOHANTA,; A. PARIARI, (The Bioscan, 2015)
To study the effect of various climatic factors on betelvine, in an established boroj, a field experiment was conducted during December 2012 to November 2013. Temperature and RH were found to be the most important factors for variation in leaf characters in different cultivars. The experiment was designed in Completely Randomized Design with eight treatments and five replications. SimuraliJhal showed superior performance with respect to leaf length (16.45 cm 2 ), leaf breadth (13.76 cm 2 ) and leaf area (274.35 cm 2 ) in rainy season. But according to storability, CARI-2 (57.75 %) perform better in winter season. In rainy season the growth and chlorophyll content (SimuraliSanchi - 2.58 mg g -1 tissue) of betel leaves was maximum, but storability was minimum (SimuraliJhal - 31.75 %).